2022
DOI: 10.1007/s00383-022-05095-1
|View full text |Cite
|
Sign up to set email alerts
|

Remote ischemic conditioning in necrotizing enterocolitis: study protocol of a multi-center phase II feasibility randomized controlled trial

Abstract: PurposeRemote ischemic conditioning (RIC) is a maneuver involving brief cycles of ischemia reperfusion in an individual's limb. In the early stage of experimental NEC, RIC decreased intestinal injury and prolonged survival by counteracting the derangements in intestinal microcirculation. A single-center phase I study demonstrated that the performance of RIC was safe in neonates with NEC. The aim of this phase II RCT was to evaluate the safety and feasibility of RIC, to identify challenges in recruitment, retai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…RIC targets the intestinal microcirculation and by improving blood flow to the intestine, reduces the intestinal damage of experimental NEC and prolongs survival [ 68 ]. A phase II feasibility randomized controlled trial involving 12 centers in 6 countries is currently underway, to investigate the feasibility of RIC as a treatment for early-stage NEC in preterm neonates [ 69 ].…”
Section: Prevention Strategy Of Necmentioning
confidence: 99%
See 1 more Smart Citation
“…RIC targets the intestinal microcirculation and by improving blood flow to the intestine, reduces the intestinal damage of experimental NEC and prolongs survival [ 68 ]. A phase II feasibility randomized controlled trial involving 12 centers in 6 countries is currently underway, to investigate the feasibility of RIC as a treatment for early-stage NEC in preterm neonates [ 69 ].…”
Section: Prevention Strategy Of Necmentioning
confidence: 99%
“…Evidence-based medicine has shown that currently, the most practical approaches to prevent NEC include optimizing maternal health care, reducing obstetric complications in mothers, and decreasing their risk of preterm birth [36]. Guiding the mother's diet and antibiotic use [17,35] Reducing obstetric complications in mothers [36] Abnormal colonization of intestinal bacteria and the microbiota Systematic use of probiotics [37,38] but is controversial [39, 40] Formula feeding and enteral nutrition Breast milk [41][42][43][44] Donor breast milk [45,46], but ethical issues need to be considered [47] Slow feeding patterns but risky [48] Infection and inflammation Interleukin 10 [51] Intra-intestinal strategies targeting TLR4 [52], such as amniotic fluid [53] and breast milk [54,55] Chondroitin sulfate [56] Local ischemia-hypoxia reperfusion Direct peritoneal resuscitation [59,60] Injury of the intestine PGE2 and its receptor PTGER4 [61] 1.5% glucose intraperitoneal infusion [62] Reducing feeding during transfusion [63] Screening congenital heart disease [64] Supplementation with arginine [65,66] Targeting HIF-1 and GLUT1 [67] Remote ischemic conditioning [68,69]…”
Section: Prevention Of Premature Delivery and Intestinal Immaturitymentioning
confidence: 99%
“…A Phase II Feasibility RCT [103] evaluating the effect of RIC on NEC is ongoing. RIC is a therapy where brief cycles of non-lethal ischemia and reperfusion to a limb results in protection from ischemic damage in distant organs.…”
Section: Remote Ischemic Conditioning (Ric) For Prevention Of Necmentioning
confidence: 99%
“…Therefore the processes within intestinal tissue which are important in the context of NEC, are not well understood and is the focus of our studies. There has already been a phase I trial on the use of RIC in human infants and the protocol for a phase II 9 , international study has been published. There is a direct pathway for translation to clinical practice.…”
Section: Introductionmentioning
confidence: 99%